Wax material, preparation method thereof and transfer paper
By adjusting the ratio in waxy materials and adding inorganic thermal fillers and glycerol, the problems of direct transfer of graphics and efficient transfer in low-temperature transfer are solved, and higher printing ink integrity and transfer efficiency are achieved.
Patent Information
- Application Number
- CN202510094496.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-21
- Publication Date
- 2025-04-25
AI Technical Summary
The prior art is difficult to achieve direct transfer of graphics and text and efficient transfer in low-temperature transfer, and the surface bearing integrity and transfer efficiency of waxy materials are low.
By adjusting the ratio of soft wax, glycerin and inorganic thermal filler, a waxy material containing inorganic thermal filler is prepared, and the material is applied to the transfer paper to improve the adhesion strength and transfer efficiency of the printing ink.
Direct transfer and efficient transfer of pictures and texts in low-temperature transfer are achieved, which improves the integrity and transfer efficiency of printing inks, and reduces the occurrence of cracks in waxy materials.
Smart Images

Figure CN119875511A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field, and in particular to a wax material and a preparation method thereof, and transfer paper. Background Art
[0002] The transfer material used as an intermediate carrier in the water transfer technique is a special polymer material, which is generally composed of three layers, the lower layer is base paper, the middle layer is a film-forming adhesive layer, and the upper layer is a hydrosol layer. The ink is printed on the hydrosol layer and transferred to the surface of the object to be transferred. The main body of the hydrosol layer is a water-soluble resin. The more commonly used water-soluble resins are polyvinyl alcohol resin, polyacrylic resin, polymethacrylic resin and polyurethane resin. Additives are further added to improve viscosity, leveling and ink adhesion effects, etc. For example, the invention patent application with application number CN202110394442.9 provides a water-based low-temperature thermal transfer adhesive with good leveling, water resistance and scratch resistance, as well as good low-temperature transfer image integrity, but its water solubility efficiency is low, that is, the ink transfer needs to be completed after the water-soluble layer is dissolved by water, while thermal transfer can effectively improve the transfer efficiency, but the transfer image method is different. For example, the invention patent application with application number CN0012 In the invention patent application No. 7292.6, a wax-like substance is used to realize rapid hot melt transfer, but the colorant is added to the wax-like substance for mixing to complete the image transfer. In the invention patent application No. CN200510049655.2, an organic purple pigment is added to wax or hardened oil for mixing to complete the image transfer. In the invention patent application No. CN201310343128.3, paraffin wax, Fischer-Tropsch wax and colorant are mixed together to complete the image transfer. The invention relates to a method for transferring a Fischer-Tropsch wax in a narrow melting range and a certain proportion of the wax. The method can improve the efficiency of thermal transfer, but the colorant and the Fischer-Tropsch wax are mixed for transfer. That is, it is difficult to support the surface graphics using only soft wax. The transfer of the specified graphics needs to be achieved through pattern control formed by hot melt, and it cannot be the same as water transfer, where the specific graphics can be directly transferred by dissolving the water-soluble layer. Summary of the invention
[0003] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a wax material and a preparation method and transfer paper that can ensure the surface bearing integrity of low-temperature transfer images and improve transfer efficiency while ensuring the direct transfer of specified images and images.
[0004] The objective of the present invention is achieved through the following technical solutions:
[0005] A waxy material comprising the following components in parts by weight:
[0006]
[0007] In one embodiment, the melting point of the soft wax is 45°C to 60°C.
[0008] In one embodiment, the thermal conductor includes colloid and inorganic thermal conductive filler.
[0009] In one embodiment, the colloid is polyethylene.
[0010] In one embodiment, the inorganic thermally conductive filler is aluminum oxide.
[0011] In one of the embodiments, the mass ratio of the colloid to the inorganic thermal conductive filler is (60-75):(8-20).
[0012] In one embodiment, the particle size of the inorganic thermally conductive filler is less than 1 μm.
[0013] In one embodiment, the viscosity enhancing agent is polyacrylamide or sodium alginate.
[0014] A method for preparing a waxy material, for preparing the waxy material described in any of the above embodiments, the method for preparing the waxy material comprising the following steps:
[0015] Get soft wax, heat transfer agent, glycerin, and viscosity enhancer;
[0016] Melting the soft wax to form liquid wax oil;
[0017] The thermal conductor, the tackifier and the glycerin are added to the liquid wax oil for mixing to obtain a waxy material.
[0018] A transfer paper comprises a base paper, an adhesive layer and a wax material layer, wherein the adhesive layer is attached to one side of the base paper, and the wax material layer is formed by coating the wax material described in any of the above embodiments on a side of the adhesive layer away from the base paper layer.
[0019] Compared with the prior art, the present invention has at least the following advantages:
[0020] The wax material of the present invention allows the thermal conductor to contain an inorganic thermal conductive filler, and the ratio of the soft wax, glycerin and the inorganic thermal conductive filler is adjusted, that is, the wax material includes 50 to 70 parts of soft wax, 10 to 15 parts of thermal conductor, 0.5 to 1 part of glycerin and 15 to 25 parts of thickener. In the wax material system, glycerin effectively improves the dispersion uniformity of the inorganic thermal conductive filler in the soft wax, and the addition of the inorganic thermal conductive filler effectively improves the adhesion strength of the printing ink on the wax material, and effectively improves the integrity of the printing ink; in addition, the addition of glycerin better improves the flexibility and film-forming effect of the soft wax, and the addition of the inorganic thermal conductive filler effectively improves the structural strength of the soft wax, thereby effectively reducing the occurrence of cracks in the wax material and further improving the integrity of the printing ink. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.
[0022] Figure 1 The present invention is a flowchart of a method for preparing a waxy material according to an embodiment of the present invention. DETAILED DESCRIPTION
[0023] In order to facilitate the understanding of the present invention, the present invention will be described more fully below with reference to the relevant drawings. The preferred embodiments of the present invention are given in the drawings. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the disclosure of the present invention more thoroughly understood.
[0024] It should be noted that when an element is referred to as being "fixed to" another element, it may be directly on the other element or there may be a central element. When an element is considered to be "connected to" another element, it may be directly connected to the other element or there may be a central element at the same time. The terms "vertical", "horizontal", "left", "right" and similar expressions used herein are for illustrative purposes only and do not represent the only implementation method.
[0025] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items.
[0026] The present application provides a wax material, which comprises the following components in parts by weight: 50 to 70 parts of soft wax, 10 to 15 parts of thermal conductor, 0.5 to 1 part of glycerin, and 15 to 25 parts of tackifier.
[0027] The above-mentioned wax material makes the thermal conductor contain inorganic thermal conductive filler, and the ratio of soft wax, glycerin and inorganic thermal conductive filler is adjusted, that is, the wax material includes 50-70 parts of soft wax, 10-15 parts of thermal conductor, 0.5-1 part of glycerin and 15-25 parts of thickener. In the wax material system, glycerin effectively improves the dispersion uniformity of inorganic thermal conductive filler in soft wax, and the addition of inorganic thermal conductive filler effectively improves the adhesion strength of printing ink on wax material, and effectively improves the integrity of printing ink; in addition, the addition of glycerin improves the flexibility and film-forming effect of soft wax, and the addition of inorganic thermal conductive filler effectively improves the structural strength of soft wax, thereby effectively reducing the occurrence of cracking of wax material and further improving the integrity of printing ink.
[0028] It can be understood that the carbon ribbon is to make the colorant mixed in the wax material and the additives so that the thermal transfer controls the formation of the pattern, that is, the wax material is the excipient of the colorant, that is, only the colorant is mixed in the wax material to realize the shaping, but it is difficult to realize the direct attachment of the colorant to the surface of the wax material in the form of a pattern. Furthermore, the adhesion effect of ink printing can be observed from the wax paper. When using wax paper for ink printing, the printing ink carried on the wax paper is seriously missing, and it is easy to cause further loss of printing ink due to external interference during transfer. In general, the adhesion of wax to printing ink is poor. In the process of ink printing and transfer, All of them will cause the loss of printing ink, which is manifested as poor ink transfer integrity. In the present application, the thermal conductor contains an inorganic thermal conductive filler, and the ratio of soft wax, glycerin and inorganic thermal conductive filler is adjusted. Glycerin effectively improves the dispersion uniformity of the inorganic thermal conductive filler in the soft wax, and the addition of the inorganic thermal conductive filler effectively improves the adhesion strength of the printing ink on the wax material, and effectively improves the integrity of the printing ink. In addition, the addition of glycerin better improves the flexibility of the soft wax, and the addition of the inorganic thermal conductive filler effectively improves the structural strength of the soft wax, thereby effectively reducing the occurrence of cracking of the wax material and further improving the integrity of the printing ink.
[0029] It should also be noted that the addition of the thickener improves the dispersion stability of the inorganic thermally conductive filler in the soft wax, and cooperates with the thermal insulation effect of the thickener's high molecular polymer, thereby enabling the thickener and the inorganic thermally conductive filler to cooperate in rapid thermal conduction and heat storage after the wax material is film-formed, thereby achieving rapid hot melt transfer of the wax material, effectively improving the transfer efficiency.
[0030] It should be noted that the addition of surfactants will cause the melting temperature range of the wax material to become wider, thereby affecting the hot melt efficiency of the wax material. It can also be understood that not only the addition of surfactants will affect the melting temperature range of the wax material, that is, the more high-temperature resistant substances are added to the wax material, and the greater the difference in the melting points of the added substances, the greater the impact on the melting temperature range of the wax material. Therefore, in the present application, the addition of glycerol not only increases the flexibility of the soft wax and promotes the dispersion effect of the inorganic thermal conductive filler, but also achieves the adhesion strength of the printing ink of the wax material in combination with the inorganic thermal conductive material, and effectively reduces the added substances in the wax material, ensuring the controllable melting temperature range of the wax material. In fact, the addition of glycerol to the wax material achieves a narrowing of the melting temperature range of the wax material, that is, the melting temperature range of the wax material after film formation is narrow and stable, and the complete hot melt transfer of the printing ink can be achieved in 1 second to 2 seconds at 100°C.
[0031] In order to better understand the wax material of the present application, the wax material of the present application is further explained below:
[0032] The wax material of one embodiment includes the following components in parts by weight: 50 to 70 parts of soft wax; 10 to 15 parts of thermal conductor; 0.5 to 1 part of glycerin; and 15 to 25 parts of tackifier.
[0033] The above-mentioned wax material makes the thermal conductor contain inorganic thermal conductive filler, and the ratio of soft wax, glycerin and inorganic thermal conductive filler is adjusted, that is, the wax material includes 50-70 parts of soft wax, 10-15 parts of thermal conductor, 0.5-1 part of glycerin and 15-25 parts of thickener. In the wax material system, glycerin effectively improves the dispersion uniformity of inorganic thermal conductive filler in soft wax, and the addition of inorganic thermal conductive filler effectively improves the adhesion strength of printing ink on wax material, and effectively improves the integrity of printing ink; in addition, the addition of glycerin improves the flexibility and film-forming effect of soft wax, and the addition of inorganic thermal conductive filler effectively improves the structural strength of soft wax, thereby effectively reducing the occurrence of cracking of wax material and further improving the integrity of printing ink.
[0034] In one embodiment, the melting point of the soft wax is 45° C. to 60° C. It should be noted that the main components of the soft wax include natural waxes such as turpentine, beeswax, and carnauba wax, which are conventional existing substances, and the soft wax is not described in detail here. Further, the soft wax comes from Foshan Hongsheng Chemical, model 160S.
[0035] In one embodiment, the thermal conductor includes a colloid and an inorganic thermal conductive filler. Further, the colloid is polyethylene, which better ensures the bonding strength of the wax material. Further, the inorganic thermal conductive filler is aluminum oxide, which better ensures the thermal conductivity of the wax material. It can be understood that the colloid is polyethylene, and is used in combination with the thermal conductive filler alumina. Since alumina is an inorganic substance, the dispersion effect of alumina in the wax material is poor, and it is easy to agglomerate and float when the wax material is coated, that is, the alumina is unevenly dispersed in the wax material, which in turn affects the hot melting efficiency and film-forming effect of the wax material. The addition of polyethylene to alumina and its use in the wax material effectively improves the compatibility of alumina in the wax material, that is, effectively reduces the agglomeration and floating of alumina when the wax material is coated, and the addition of polyethylene effectively reduces the effect of the addition of alumina in the wax material on its flexibility, that is, the thermal conductor includes polyethylene and alumina, which effectively ensures the dispersion stability of alumina in the wax material, and then the ink adhesion effect of the wax material, while better ensuring the flexibility and film-forming effect of the wax material, effectively reducing the occurrence of cracking of the wax material after film formation, and also improving the structural strength of the wax material after film formation, further reducing the occurrence of cracking of the wax material after film formation.
[0036] In one embodiment, the mass ratio of the colloid and the inorganic thermal conductive filler is (60-75): (8-20). It should be noted that the amount of the inorganic thermal conductive filler used in the wax material has a great influence on the adhesion effect of the ink on the surface of the wax material. If the amount of the inorganic thermal conductive filler used is too small, the adhesion effect of the ink is poor, and if the amount of the inorganic thermal conductive filler used is too large, it will affect the overall flexibility and film-forming effect of the wax material. Therefore, the thermal conductor is 10 to 15 parts, and the mass ratio of the colloid and the inorganic thermal conductive filler is (60 to 75): (8 to 20), and further with 50 to 70 parts of soft wax, 0.5 to 1 part of glycerin and 15 to 25 parts of thickener, the adhesion effect of the ink on the surface of the wax material is effectively ensured, and the film-forming effect and flexibility of the wax material are better ensured. Further, the mass ratio of the colloid and the inorganic thermal conductive filler is 67:13. The adhesion effect of ink on the surface of the wax material is further improved, and the film-forming effect and flexibility of the wax material are better improved.
[0037] In one embodiment, the particle size of the inorganic thermal conductive filler is less than 1 μm. Further, the particle size D50 of the inorganic thermal conductive filler is 0.1 μm to 0.3 μm, which better ensures the adhesion of the ink on the surface of the wax material and better improves the film-forming effect and flexibility of the wax material.
[0038] In one embodiment, the thickener is polyacrylamide or sodium alginate. It is understood that if the thickener is a short-chain thickener, the dispersion stability of the inorganic thermal conductive filler in the soft wax is poor, and if the thickener is a network structure thickener, the structural strength of the soft wax and the inorganic thermal conductive filler is high, which affects the hot melting efficiency of the wax material after film formation.
[0039] The present application also provides a method for preparing a wax material, which is used to prepare the wax material of any of the above embodiments. The above method for preparing a wax material comprises the following steps: obtaining soft wax, a thermal conductor, glycerin and a tackifier; melting the soft wax to form liquid wax oil; adding a thermal conductor, a tackifier and glycerin to the liquid wax oil for mixing to obtain a wax material.
[0040] In order to better understand the preparation method of the wax material of the present application, the preparation method of the wax material of the present application is further explained below:
[0041] See also Figure 1 A method for preparing a waxy material in one embodiment comprises the following steps:
[0042] S100, obtaining soft wax, thermal conductive agent, glycerin and tackifier;
[0043] S200, melting the soft wax to form liquid wax oil;
[0044] S300, adding a heat conductor, a tackifier and glycerin to the liquid wax oil for mixing to obtain a waxy material.
[0045] The above-mentioned method for preparing the waxy material realizes the effective preparation of the waxy material.
[0046] In one embodiment, a thermal conductive agent, a tackifier and glycerin are added to liquid wax oil for mixing, and the steps are as follows:
[0047] Add a heat conductor and a tackifier to the liquid wax oil for a mixing process. Further, after adding a heat conductor to the special wax oil for mixing, the tackifier is added to the liquid wax oil for mixing under continuous stirring. Further, the mixing speed is 100r / min to 200r / min. Further, the mixing is performed for 5min to 8min after each addition of the substance.
[0048] Further, glycerol is added to the liquid wax oil after the primary mixing process for secondary mixing process. Further, glycerol is added to the liquid wax oil after the primary mixing process for secondary mixing process in a dry environment. Further, the mixing speed is 100r / min to 200r / min. Further, the mixing time is 10min to 15min.
[0049] It can be understood that the viscosity of the liquid wax oil will increase after the addition of thickener and glycerol. Therefore, the thermal conductor is first added to the liquid wax oil for mixing, which effectively improves the dispersion efficiency of the thermal conductor. Furthermore, since glycerol is added to the liquid wax oil, the viscosity of the liquid wax oil will increase, and the hygroscopicity of the liquid wax oil will be enhanced, which will pose a safety hazard in the preparation process. Therefore, after the thermal conductor is evenly mixed with the liquid wax oil, the thickener is further added to the liquid wax oil for even mixing, and finally glycerol is added to the liquid wax oil for even mixing, which effectively realizes the effective preparation of the wax material and better ensures the safety of the preparation of the wax material.
[0050] The present application also provides a transfer paper, including base paper, an adhesive layer and a wax material layer, the adhesive layer is attached to one side of the base paper, and the wax material layer is formed by applying the wax material of any of the above embodiments to the side of the adhesive layer away from the base paper layer. Further, the base paper includes a substrate layer and a calcium carbonate layer, and the adhesive layer is attached to the calcium carbonate layer. Further, the substrate layer includes coniferous wood pulp, broadleaf wood pulp and porcelain clay filler. It can be understood that the main material of the substrate layer is coniferous wood pulp, broadleaf wood pulp and porcelain clay filler, which is a substrate layer prepared by an existing conventional preparation method, so the substrate layer is not described in detail here. Further, the base paper comes from Shandong Henglian Paper. Further, the adhesive layer includes potato starch and water. It can be understood that the main material of the adhesive layer is potato starch and water, which is an adhesive layer prepared by an existing conventional preparation method, so the adhesive layer is not described in detail here. Further, a back adhesive layer is adhered to the side of the base paper away from the adhesive layer. Further, the back adhesive layer includes wheat starch and water. It can be understood that the main materials of the back adhesive layer are wheat starch and water, and the back adhesive layer is prepared by the existing conventional preparation method. Therefore, the back adhesive layer will not be described in detail here.
[0051] In one embodiment, the thickness of the substrate layer is 190 μm and the surface density is 150 g / m 2 Furthermore, the thickness of the calcium carbonate layer is 10 μm and the surface density is 25 g / m 2 Furthermore, the thickness of the adhesive layer is 5 μm and the surface density is 5 g / m 2 Furthermore, the thickness of the back adhesive layer is 2 μm and the surface density is 2 g / m 2 Furthermore, the wax material layer has a thickness of 5 μm and a surface density of 5 g / m 2 .
[0052] Compared with the prior art, the present invention has at least the following advantages:
[0053] The wax material of the present invention allows the thermal conductor to contain an inorganic thermal conductive filler, and the ratio of the soft wax, glycerin and the inorganic thermal conductive filler is adjusted, that is, the wax material includes 50 to 70 parts of soft wax, 10 to 15 parts of thermal conductor, 0.5 to 1 part of glycerin and 15 to 25 parts of thickener. In the wax material system, glycerin effectively improves the dispersion uniformity of the inorganic thermal conductive filler in the soft wax, and the addition of the inorganic thermal conductive filler effectively improves the adhesion strength of the printing ink on the wax material, and effectively improves the integrity of the printing ink; in addition, the addition of glycerin better improves the flexibility and film-forming effect of the soft wax, and the addition of the inorganic thermal conductive filler effectively improves the structural strength of the soft wax, thereby effectively reducing the occurrence of cracks in the wax material and further improving the integrity of the printing ink.
[0054] Some specific examples are given below, and if % is mentioned, it means percentage by weight. It should be noted that the following examples do not exhaust all possible situations, and the materials used in the following examples can be obtained from commercial sources unless otherwise specified.
[0055] Example 1
[0056] Obtain 7 kg of soft wax (from Foshan Hongsheng Chemical, model 160S), 1.5 kg of alumina and polyethylene (the mass ratio of alumina to polyethylene is 75:20, and the particle size D50 of alumina is 0.2 μm), 0.1 kg of glycerol, and 2.5 kg of polyacrylamide;
[0057] The soft wax is melted at high temperature to form liquid wax oil, aluminum oxide and polyethylene are added to the liquid wax oil and mixed for 6 minutes at a mixing speed of 150 r / min, then polyacrylamide is added and mixed for 6 minutes at a mixing speed of 150 r / min, then glycerol is added and mixed for 12 minutes at a mixing speed of 150 r / min to obtain a waxy material;
[0058] The semi-finished transfer paper was obtained, wherein the thickness of the substrate layer was 190 μm and the surface density was 150 g / m 2 , from Shandong Henglian Paper; the thickness of the calcium carbonate layer is 10μm and the surface density is 25g / m 2 ; The thickness of the adhesive layer is 5μm and the surface density is 5g / m 2 ; The thickness of the back adhesive layer is 2μm and the surface density is 2g / m 2 Then, a wax material is coated on the adhesive layer using a scraper to form a wax material layer. The wax material layer has a thickness of 5 μm and a surface density of 5 g / m 2 , get transfer paper.
[0059] Example 2
[0060] Obtain 6 kg of soft wax (from Foshan Hongsheng Chemical, model 160S), 1.2 kg of alumina and polyethylene (the mass ratio of alumina to polyethylene is 67:13, and the particle size D50 of alumina is 0.2 μm), 0.08 kg of glycerol, and 2 kg of polyacrylamide;
[0061] The soft wax is melted at high temperature to form liquid wax oil, aluminum oxide and polyethylene are added to the liquid wax oil and mixed for 6 minutes at a mixing speed of 150 r / min, then polyacrylamide is added and mixed for 6 minutes at a mixing speed of 150 r / min, then glycerol is added and mixed for 12 minutes at a mixing speed of 150 r / min to obtain a waxy material;
[0062] The semi-finished transfer paper was obtained, wherein the thickness of the substrate layer was 190 μm and the surface density was 150 g / m 2 , from Shandong Henglian Paper; the thickness of the calcium carbonate layer is 10μm and the surface density is 25g / m 2 ; The thickness of the adhesive layer is 5μm and the surface density is 5g / m 2 ; The thickness of the back adhesive layer is 2μm and the surface density is 2g / m 2 Then, a wax material is coated on the adhesive layer using a scraper to form a wax material layer. The wax material layer has a thickness of 5 μm and a surface density of 5 g / m 2 , get transfer paper.
[0063] Example 3
[0064] Obtain 5 kg of soft wax (from Foshan Hongsheng Chemical, model 160S), 1 kg of alumina and polyethylene (the mass ratio of alumina to polyethylene is 60:8, and the particle size D50 of alumina is 0.2 μm), 0.05 kg of glycerol, and 1.5 kg of polyacrylamide;
[0065] The soft wax is melted at high temperature to form liquid wax oil, aluminum oxide and polyethylene are added to the liquid wax oil and mixed for 6 minutes at a mixing speed of 150 r / min, then polyacrylamide is added and mixed for 6 minutes at a mixing speed of 150 r / min, then glycerol is added and mixed for 12 minutes at a mixing speed of 150 r / min to obtain a waxy material;
[0066] The semi-finished transfer paper was obtained, wherein the thickness of the substrate layer was 190 μm and the surface density was 150 g / m 2 , from Shandong Henglian Paper; the thickness of the calcium carbonate layer is 10μm and the surface density is 25g / m 2 ; The thickness of the adhesive layer is 5μm and the surface density is 5g / m 2 ; The thickness of the back adhesive layer is 2μm and the surface density is 2g / m 2Then, a wax material is coated on the adhesive layer using a scraper to form a wax material layer. The wax material layer has a thickness of 5 μm and a surface density of 5 g / m 2 , get transfer paper.
[0067] Example 4
[0068] Obtain 6 kg of soft wax (from Foshan Hongsheng Chemical, model 160S), 1.2 kg of alumina and polyethylene (the mass ratio of alumina to polyethylene is 67:13, and the particle size D50 of alumina is 0.2 μm), 0.08 kg of glycerol, and 2 kg of sodium alginate;
[0069] The soft wax is melted at high temperature to form liquid wax oil, aluminum oxide and polyethylene are added to the liquid wax oil and mixed for 6 minutes at a mixing speed of 150 r / min, then sodium alginate is added and mixed for 6 minutes at a mixing speed of 150 r / min, then glycerol is added and mixed for 12 minutes at a mixing speed of 150 r / min to obtain a waxy material;
[0070] The semi-finished transfer paper was obtained, wherein the thickness of the substrate layer was 190 μm and the surface density was 150 g / m 2 , from Shandong Henglian Paper; the thickness of the calcium carbonate layer is 10μm and the surface density is 25g / m 2 ; The thickness of the adhesive layer is 5μm and the surface density is 5g / m 2 ; The thickness of the back adhesive layer is 2μm and the surface density is 2g / m 2 Then, a wax material is coated on the adhesive layer using a scraper to form a wax material layer. The wax material layer has a thickness of 5 μm and a surface density of 5 g / m 2 , get transfer paper.
[0071] Example 5
[0072] Obtain 6 kg of soft wax (from Foshan Hongsheng Chemical, model 160S), 1.2 kg of alumina and polyethylene (the mass ratio of alumina to polyethylene is 67:13, and the particle size D50 of alumina is 0.1 μm), 0.08 kg of glycerol, and 2 kg of polyacrylamide;
[0073] The soft wax is melted at high temperature to form liquid wax oil, aluminum oxide and polyethylene are added to the liquid wax oil and mixed for 6 minutes at a mixing speed of 150 r / min, then polyacrylamide is added and mixed for 6 minutes at a mixing speed of 150 r / min, then glycerol is added and mixed for 12 minutes at a mixing speed of 150 r / min to obtain a waxy material;
[0074] The semi-finished transfer paper was obtained, wherein the thickness of the substrate layer was 190 μm and the surface density was 150 g / m 2, from Shandong Henglian Paper; the thickness of the calcium carbonate layer is 10μm and the surface density is 25g / m 2 ; The thickness of the adhesive layer is 5μm and the surface density is 5g / m 2 ; The thickness of the back adhesive layer is 2μm and the surface density is 2g / m 2 Then, a wax material is coated on the adhesive layer using a scraper to form a wax material layer. The wax material layer has a thickness of 5 μm and a surface density of 5 g / m 2 , get transfer paper.
[0075] Example 6
[0076] Obtain 6 kg of soft wax (from Foshan Hongsheng Chemical, model 160S), 1.2 kg of alumina and polyethylene (the mass ratio of alumina to polyethylene is 67:13, and the particle size D50 of alumina is 0.3 μm), 0.08 kg of glycerol, and 2 kg of polyacrylamide;
[0077] The soft wax is melted at high temperature to form liquid wax oil, aluminum oxide and polyethylene are added to the liquid wax oil and mixed for 6 minutes at a mixing speed of 150 r / min, then polyacrylamide is added and mixed for 6 minutes at a mixing speed of 150 r / min, then glycerol is added and mixed for 12 minutes at a mixing speed of 150 r / min to obtain a waxy material;
[0078] The semi-finished transfer paper was obtained, wherein the thickness of the substrate layer was 190 μm and the surface density was 150 g / m 2 , from Shandong Henglian Paper; the thickness of the calcium carbonate layer is 10μm and the surface density is 25g / m 2 ; The thickness of the adhesive layer is 5μm and the surface density is 5g / m 2 ; The thickness of the back adhesive layer is 2μm and the surface density is 2g / m 2 Then, a wax material is coated on the adhesive layer using a scraper to form a wax material layer. The wax material layer has a thickness of 5 μm and a surface density of 5 g / m 2 , get transfer paper.
[0079] Comparative Example 1
[0080] Obtain 6 kg of soft wax (from Foshan Hongsheng Chemical, model 160S), 1.2 kg of alumina and polyethylene (the mass ratio of alumina to polyethylene is 67:13, and the particle size D50 of alumina is 0.2 μm), 0.08 kg of glycerol, and 2 kg of polyacrylamide;
[0081] The soft wax is melted at high temperature to form liquid wax oil, and aluminum oxide, polyethylene, polyacrylamide and glycerol are added to the liquid wax oil and mixed for 25 minutes at a mixing speed of 150 r / min to obtain a waxy material;
[0082] The semi-finished transfer paper was obtained, wherein the thickness of the substrate layer was 190 μm and the surface density was 150 g / m 2 , from Shandong Henglian Paper; the thickness of the calcium carbonate layer is 10μm and the surface density is 25g / m 2 ; The thickness of the adhesive layer is 5μm and the surface density is 5g / m 2 ; The thickness of the back adhesive layer is 2μm and the surface density is 2g / m 2 Then, a wax material is coated on the adhesive layer using a scraper to form a wax material layer. The wax material layer has a thickness of 5 μm and a surface density of 5 g / m 2 , get transfer paper.
[0083] Comparative Example 2
[0084] Obtain 6 kg of soft wax (from Foshan Hongsheng Chemical, model 160S), alumina and polyethylene in total 1.2 kg (the mass ratio of alumina to polyethylene is 67:13, and the particle size D50 of alumina is 0.2 μm);
[0085] The soft wax is melted at high temperature to form liquid wax oil, and aluminum oxide and polyethylene are added to the liquid wax oil and mixed for 6 minutes at a mixing speed of 150 r / min to obtain a waxy material;
[0086] The semi-finished transfer paper was obtained, wherein the thickness of the substrate layer was 190 μm and the surface density was 150 g / m 2 , from Shandong Henglian Paper; the thickness of the calcium carbonate layer is 10μm and the surface density is 25g / m 2 ; The thickness of the adhesive layer is 5μm and the surface density is 5g / m 2 ; The thickness of the back adhesive layer is 2μm and the surface density is 2g / m 2 Then, a wax material is coated on the adhesive layer using a scraper to form a wax material layer. The wax material layer has a thickness of 5 μm and a surface density of 5 g / m 2 , get transfer paper.
[0087] Comparative Example 3
[0088] Obtain 6 kg of soft wax (from Foshan Hongsheng Chemical, model 160S), 1.2 kg of alumina and polyethylene (the mass ratio of alumina to polyethylene is 67:13, and the particle size D50 of alumina is 0.2 μm), and 2 kg of polyacrylamide;
[0089] The soft wax is melted at high temperature to form liquid wax oil, aluminum oxide and polyethylene are added to the liquid wax oil and mixed for 6 minutes at a mixing speed of 150 r / min, and then polyacrylamide is added and mixed for 6 minutes at a mixing speed of 150 r / min to obtain a waxy material;
[0090] The semi-finished transfer paper was obtained, wherein the thickness of the substrate layer was 190 μm and the surface density was 150 g / m 2 , from Shandong Henglian Paper; the thickness of the calcium carbonate layer is 10μm and the surface density is 25g / m 2 ; The thickness of the adhesive layer is 5μm and the surface density is 5g / m 2 ; The thickness of the back adhesive layer is 2μm and the surface density is 2g / m 2 Then, a wax material is coated on the adhesive layer using a scraper to form a wax material layer. The wax material layer has a thickness of 5 μm and a surface density of 5 g / m 2 , get transfer paper.
[0091] Comparative Example 4
[0092] Obtain 6 kg of soft wax (from Foshan Hongsheng Chemical, model 160S), 1.2 kg of alumina and polyethylene (the mass ratio of alumina to polyethylene is 67:13, and the particle size D50 of alumina is 0.2 μm), 0.08 kg of glycerol, and 2 kg of polyacrylamide;
[0093] The soft wax is melted at high temperature to form liquid wax oil, aluminum oxide and polyethylene are added to the liquid wax oil and mixed for 6 minutes at a mixing speed of 150 r / min, then polyacrylamide is added and mixed for 6 minutes at a mixing speed of 150 r / min, then glycerol is added and mixed for 12 minutes at a mixing speed of 150 r / min to obtain a waxy material;
[0094] The semi-finished transfer paper was obtained, wherein the thickness of the substrate layer was 150 μm and the surface density was 100 g / m 2 , from Shandong Henglian Paper; the thickness of the calcium carbonate layer is 20μm and the surface density is 30g / m 2 ; The thickness of the adhesive layer is 3μm and the surface density is 3g / m 2 ; The thickness of the back adhesive layer is 8μm and the surface density is 5g / m 2 Then, a wax material is coated on the adhesive layer using a scraper to form a wax material layer. The wax material layer has a thickness of 15 μm and a surface density of 8 g / m 2 , get transfer paper.
[0095] The wax materials and transfer papers obtained in Examples 1 to 6 and Comparative Examples 1 to 4 were observed below, and the transfer papers were subjected to ink printing transfer. The specifications of the transfer papers were all 10 cm*10 cm, and the amount of ink used on the transfer paper during printing was 20 g / m 2 , the transfer paper after printing ink is tested for printing ink, and recorded, and whether there are cracks on the transfer paper is recorded, the results are shown in Table 1:
[0096] Table 1:
[0097]
[0098]
[0099] It can be seen from Table 1 that, compared with the wax material of Comparative Example 1, the wax materials of Examples 1 to 6 have higher preparation efficiency, while the wax material in Comparative Example 1 has poor mixing effect within the same time, which affects the film-forming effect, resulting in obvious cracking of the wax material layer after film formation, which is further reflected in the reduced ink adhesion stock on the transfer paper and poor integrity; compared with the transfer paper of Comparative Examples 2 to 3, the transfer speed of Examples 1 to 6 is greatly accelerated, and the film-forming effect is better, which can effectively ensure the adhesion integrity of the printing ink, especially the transfer speed of Examples 2 and 4 is faster; in addition, compared with the transfer paper of Comparative Example 4, it can be seen that the thickness and surface density of the pulp paper substrate, back glue coating, calcium carbonate coating, base glue coating and wax material layer in the transfer paper have a certain influence on the adhesion integrity and transfer effect of the printing ink.
[0100] The above embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for those of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A waxy material, characterized in that: The composition comprises the following components in parts by weight: The thermal conductive agent contains an inorganic thermal conductive filler.
2. The wax material according to claim 1, characterized in that: The melting point of the soft wax is 45°C to 60°C.
3. The wax material according to claim 1, characterized in that: The thermal conductor includes colloid and inorganic thermal conductive filler.
4. The wax material according to claim 3, characterized in that: The colloid is polyethylene.
5. The wax material according to claim 3, characterized in that: The inorganic thermal conductive filler is aluminum oxide.
6. The wax material according to claim 3, characterized in that: The mass ratio of the colloid to the inorganic thermal conductive filler is (60-75):(8-20).
7. The wax material according to claim 3, characterized in that: The particle size of the inorganic thermal conductive filler is less than 1 μm.
8. The wax material according to claim 1, characterized in that: The viscosity enhancer is polyacrylamide or sodium alginate.
9. A method for preparing a waxy material, for preparing the waxy material according to any one of claims 1 to 8, characterized in that: The preparation method of the waxy material comprises the following steps: Get soft wax, heat transfer agent, glycerin, and viscosity enhancer; Melting the soft wax to form liquid wax oil; The thermal conductor, the tackifier and the glycerin are added to the liquid wax oil for mixing to obtain a waxy material.
10. A transfer paper, characterized in that: The invention comprises a base paper, an adhesive layer and a wax material layer, wherein the adhesive layer is attached to one side of the base paper, and the wax material layer is formed by coating the wax material according to any one of claims 1 to 8 on a side of the adhesive layer away from the base paper layer.
Citation Information
Patent Citations
Improved drainge valve and open-close method
CN100353004C
Wax special for heat transfer printing and manufacturing method thereof
CN104341780A
A heat transfer wax and its preparation method
CN111286361B
Water-based low-temperature heat transfer printing adhesive and preparation method thereof
CN113025233A
Heat transfer colour ribbon
CN1351933A